Recent Advances of Fluorescence Probes for Imaging of Ferroptosis Process - Hongyu Li; Yan An; Jie Gao; Mingyan Yang; Junjun Luo; Xinmin Li; Jiajia Lv; Xiaohua Li; Zeli Yuan; Huimin Ma (Chemosensors, 2022)
Ferroptosis is an iron−dependent form of regulated cell death. It has attracted more and more research interests since it was found because of its potential physiological and pathological roles. In recent years, many efforts have been made for the developments and applications of selective fluorescence probes for real−time and in situ tracking of bioactive species during ferroptosis process, which is necessary and significant to further study the modulation mechanisms and pathological functions of ferroptosis. In this review, we will focus on summarizing the newly developed fluorescence probes that have been applied for ferroptosis imaging in the recent years, and comprehensively discussing their design strategies, including the probes for iron, reactive oxygen species, biothiols and intracellular microenvironmental factors.